2015
DOI: 10.1002/pssr.201510086
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence enhancement in ultraviolet organic light‐emitting diode with graded hole‐injection and ‐transporting structure

Abstract: Electroluminescent intensity and external quantum efficiency (EQE) in ultraviolet organic light‐emitting diodes (UV OLEDs) have been remarkably enhanced by using a graded hole‐injection and ‐transporting (HIT) structure of MoO3/N,N ′‐bis(naphthalen‐1‐yl)‐N,N ′‐bis(phenyl)‐benzidine/MoO3/4,4′‐bis(carbazol‐9‐yl)biphenyl (CBP). The graded‐HIT based UV OLED shows superior short‐wavelength emis‐ sion with spectral peak of ∼410 nm, maximum electroluminescent intensity of 2.2 mW/cm2 at 215 mA/cm2 and an EQE of 0.72% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…5b). Owing to the high work function that matches the energy level better, and the lower sheet resistance, the turn on and operation voltage are relative lower compare to the reported results26. The output power and EL spectra were measured by PM310E (thorlabs), Avantes fiber spectrometer.…”
Section: Resultsmentioning
confidence: 94%
“…5b). Owing to the high work function that matches the energy level better, and the lower sheet resistance, the turn on and operation voltage are relative lower compare to the reported results26. The output power and EL spectra were measured by PM310E (thorlabs), Avantes fiber spectrometer.…”
Section: Resultsmentioning
confidence: 94%
“…For many small-molecule organic semiconductor materials, the dielectric permittivity at optical frequencies is known from thin-film ellipsometry measurements [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], electron energy loss spectroscopy [27], and from theory using quantum-chemically calculated molecular polarizabilities and the Clausius-Mossotti relationship [28,29]. The relative dielectric constant at quasistatic conditions may be obtained from low-frequency capacitance-voltage (C-V) studies of sandwich-type devices [30][31][32][33][34][35][36][37][38][39]. In principle, the dielectric permittivity in the full frequency range of interest can be obtained by combining the results of f -dependent C-V measurements (dielectric spectroscopy [40]), terahertz, infrared, and optical spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…These structures can intuitively display the above theories, such as the devices with hole injection layers of Ag 2 O/MoO x , MoO 3 /NPB/MoO 3 /CBP, as even the concentration gradient provided a stepped energy level, which greatly facilitated hole injection and, hence, enhanced the injection current [ 89 , 90 , 91 ]. It has been reported that the presence of charge transfer between MoO 3 and NPB is also conductive to hole injection [ 92 , 93 ].…”
Section: Composite Hole Injection Layer Structurementioning
confidence: 99%